How cultural beliefs and rituals may help alleviate grief and despair: a four-dimensional framework - Phan, Huy P.; Ngu, Bing Hiong; Chen, Si-Chi; Hsu, Chao-Sheng (Frontiers in Sociology, 2025)
This theoretical-conceptual article draws on philosophical discourse, cultural analysis, and personal narrative accounts from our teaching and research in life and death education, particularly within higher education settings, to examine the important role of cultural grief rituals in contemporary bereavement practices. Focusing on traditions such as ancestor worship, we explore how such rituals provide structured frameworks for processing grief, fostering emotional resilience, and sustaining meaningful connections with the deceased. We propose that these culturally embedded practices can function as contemporary ‘grief support systems’, offering pedagogical and existential insights for individuals navigating death, loss, and mourning. Through cross-cultural examples (e.g., from East Asian, Indigenous, African diasporic, and Western contexts), we attempt to explain how grief rituals (e.g., the practice of ancestor worship) may foster empathy, promote cultural literacy, and help individuals and communities reframe loss in constructive, inclusive ways. In doing so, the article underscores the importance of integrating cultural heritage and its appreciation into life and death education curricula, fostering more holistic and culturally responsive approaches to the teaching and research of the subject, including grief. Finally, we propose a theoretical model—named as the ‘Four-Dimensional Framework for Understanding Cultural Grief Rituals’—which serves to delineate the emotional, communal, cross-cultural, and spiritual functions of these practices. This proposed framework not only informs future sociocultural research on bereavement but also offers practical pathways for enhancing grief education and support strategies in increasingly diverse and globalized learning environments.